2013
DOI: 10.1210/en.2012-1772
|View full text |Cite
|
Sign up to set email alerts
|

Characterization, Neurosteroid Binding and Brain Distribution of Human Membrane Progesterone Receptors δ and ϵ (mPRδ and mPRϵ) and mPRδ Involvement in Neurosteroid Inhibition of Apoptosis

Abstract: Three members of the progestin and adipoQ receptor (PAQR) family, PAQR-7, PAQR-8, and PAQR-5 [membrane progesterone (P4) receptor (PR) (mPR)α, mPRβ, and mPRγ], function as plasma mPRs coupled to G proteins in mammalian cells, but the characteristics of two other members, PAQR6 and PAQR9 (mPRδ and mPRε), remain unclear, because they have only been investigated in yeast expression systems. Here, we show that recombinant human mPRδ and mPRε expressed in MDA-MB-231 breast cancer cells display specific, saturable, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
178
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(194 citation statements)
references
References 46 publications
11
178
0
1
Order By: Relevance
“…Other, recent data suggest that, as part of the cellular response to the binding of progesterone to mPRα, apoptosis is inhibited in breast cancer cells (8)(9)(10). In the membranes of neuroendocrine cells, mPRs appear to interact with G proteins and have a role in the release of hormones and maintain oocyte maturation by regulating gonadotropin releasing hormone (GnRH) secretion (24). Progesterone is known to have neuroprotective effects, which possibly is mediated by mPRα.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other, recent data suggest that, as part of the cellular response to the binding of progesterone to mPRα, apoptosis is inhibited in breast cancer cells (8)(9)(10). In the membranes of neuroendocrine cells, mPRs appear to interact with G proteins and have a role in the release of hormones and maintain oocyte maturation by regulating gonadotropin releasing hormone (GnRH) secretion (24). Progesterone is known to have neuroprotective effects, which possibly is mediated by mPRα.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, based on the analyses of proteins expressed in yeast, mPRδ and ε (PAQR6 and 9) were proposed to form novel mPR subtypes (31). Also human orthologs of them, when expressed in human breast cancer cells, were found to have progestin binding activity (24). Therefore, five mPR subtypes have been described at present.…”
mentioning
confidence: 99%
“…Furthermore, a family of membrane progesterone receptors (mPRs) has been found that mediates rapid actions of P ( Figure 1). This non-genomic mechanism has been described in some cellular functions in females such as: oocyte meiotic maturation, GnRH secretion, reproductive behavior, apoptosis of granulose, breast cancer and neuronal cells [14][15][16][17] . These mPRs are G-protein-coupled and function following the cAMP cascade ( Figure 1).…”
Section: Introductionmentioning
confidence: 97%
“…PROG-induced nongenomic activity is mainly mediated by two different membrane-bound PROG receptor types: the seven-transmembrane progesterone adiponectin Q receptors (PAQR) and the single-transmembrane PGRs (Thomas 2008. The former are G protein-coupled membrane receptors and include three subtypes of receptors: PROG membrane receptors (mPGR) α, β, and γ, also referred to as transmembrane PGRs α, β, or γ (7TMPRα,β,γ) and the two more recently identified subtypes mPGRδ and mPGRε (Pang et al 2013, Hossain et al 2015. When bound to its ligand, these receptors block adenylate cyclase activity to reduce excitation in the CNS , Thomas 2008, Do Rego et al 2009, King 2013.…”
Section: Introductionmentioning
confidence: 99%